2014
DOI: 10.1038/ajg.2013.421
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Use of Over-the-Counter Proton Pump Inhibitors in Patients With Gastroesophageal Reflux Disease

Abstract: Patients receiving prescription PPI from a GI are more likely to be optimal users with better symptom control. Conversely, consumers are more likely to be suboptimal users with inadequate symptom control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…However, more than 50% of GERD patients do not adhere to proper timing of PPI consumption when prescribed by a primary care physician. 88 Gunaratnam et al 89 showed that only 46% of refractory GERD patients were dosing their PPI optimally. Of those who dosed suboptimally, 39% took their PPI at bedtime, and 4% took it as needed.…”
Section: Dependency On Food For Efficacymentioning
confidence: 99%
“…However, more than 50% of GERD patients do not adhere to proper timing of PPI consumption when prescribed by a primary care physician. 88 Gunaratnam et al 89 showed that only 46% of refractory GERD patients were dosing their PPI optimally. Of those who dosed suboptimally, 39% took their PPI at bedtime, and 4% took it as needed.…”
Section: Dependency On Food For Efficacymentioning
confidence: 99%
“…Although the proportion of patients taking OTC PPIs internationally is unknown, it may well represent the majority of use globally. A recent US survey [433] found that 32 % of patients with GERD symptoms were using OTC PPIs, with only 39 % of consumers using them optimally, with better symptom relief. Besides patients, 50 % of US gastroenterologists also use (i.e., suggest to patients) OTC PPIs [434].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that azeloprazole sodium may be more effective when administered before a meal, as in the report about other PPIs. 13,14 Further study should be performed to show a definite difference or similarity before and after a meal.…”
Section: Discussionmentioning
confidence: 99%
“…Although the labels of most PPIs do not provide a recommended dosing time, PPIs should be taken before meals because they optimally suppress acid secretion when parietal cells are activated after food intake. 13,14 However, the preferred dosing time should be determined based on evidence; therefore, it is important to assess the effect of food on the pharmacokinetics (PK) and pharmacodynamics (PD) of PPIs. Azeloprazole sodium was synthesized to overcome issues associated with the metabolism of marketed PPIs by CYP2C19.…”
mentioning
confidence: 99%